NBP‐based icosϕ control strategy for DSTATCOM. Issue 12 (1st October 2017) - Mangaraj, Mrutyunjaya; Panda, Anup Kumar
Abstract : A propounded control strategy called naive back propagation (NBP)‐based i cos ϕ is implemented in designing of distribution static compensator (DSTATCOM) in this study. The performance of the DSTATCOM using both the proposed and i cos ϕ control technique are compared under varying load condition in the three‐phase three‐wire (3P3W) distribution system. The extraction of both tuned active as well as reactive weighting components are obtained from the accuracy of the control algorithm with respect to proportional–integral controllers. The comparative study reveals with source current harmonics reduction, voltage regulation, load balancing, power factor correction and sizing of VSC. The results demonstrate the robustness of the DSTATCOM in order to show the superiority, reliability, robustness and effectiveness of the proposed approach compared with the conventional one. The effectiveness of both the algorithms are validated through the simulation using MATLAB and real‐time implementation conducted in real time digital simulator (RTDS) environment, showing the power quality indices.